Sustainability-driven additive manufacturing: Implementation and content optimization of fine powder recycled glass in polylactic acid for material extrusion 3D printing - Markos Petousis; Nikolaos Michailidis; Václav Kulas; Vassilis Papadakis; Mariza Spiridaki; Nikolaos Mountakis; Apostolos Argyros; John Valsamos; Nektarios K. Nasikas; Nectarios Vidakis (International Journal of Lightweight Materials and Manufacture)
This work aimed to evaluate the capacity of recycled fine powder glass (RFPG) to reinforce the mechanical performance and characteristics of polylactic acid (PLA) for use in 3D printing (3DP) applications. Six composites with an RFPG filler quantity of 2.0 wt % −12.0 wt % (with a 2.0 step) were evaluated. The raw materials were turned into mixtures, which then fabricated respective filaments. The filaments were inspected and tested for their properties before being utilized to produce the specimens for testing with 3DP. The structures, morphologies, and mechanical properties of the specimens were examined by performing respective tests, scanning electron microscopy, and micro-computed tomography (μ-CT). Moreover, the samples were tested for their thermal properties through thermogravimetric and differential scanning calorimetry analyses, and for their rheological performance. Quality metrics were evaluated with μ-CT (porosity and dimensional accuracy). The findings indicated that RFPG as a filler reinforced the PLA matrix, in the case of 6.0 wt % (23.6 % and 28.7 % strength enhancement in the flexural and tensile tests respectively). The thermal properties were insignificantly changed with a small increase in the crystallization temperature, while the viscosity was significantly lowered with the increase of the powder content in the compounds. The quality metrics were enhanced as well, making this specific RFPG grade a promising filler for the PLA matrix in 3D printing.